A histopathological study of hysterectomy specimens and their clinical correlation in patients at tertiary health care setup in Bundelkhand region of Uttar Pradesh - Agarwal, Sippy; Sharma, Seema; Pandey, Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Women in their life time are prone to develop several neoplastic and non-neoplastic lesions in her uterus and cervix basically due to hormone responsiveness of female genital tract system. The aim of the study was to evaluate all hysterectomy specimens and to study the pattern of pathological changes of different lesions occurring in cervix and uterus associated with different age groups. Methods: This retrospective cross-sectional, study was conducted on patients undergoing hysterectomy in department of obstetrics and gynecology in MLB Medical College Jhansi and hysterectomized specimens reported to department of pathology for further evaluation. Total 35 hysterectomy specimens were included in the study with age of patients varying from 30 years to 60 years. Detailed clinical and other relevant history were taken followed by thorough gross examination and histopathological evaluation. Results: Majority of hysterectomy specimens were sent for histopathological examination in the department of pathology, out of these 30 (85%) were total abdominal hysterectomy specimen, 5 (14.28%) were of vaginal hysterectomy specimens. Out of all these cases, in 7 (20%) cases bilateral or unilateral salpingopherectomy done. Conclusions: In our study, most common surgical procedure for hysterectomy was abdominal hysterectomy 30 (85.7%) followed vaginal hysterectomy 5 (14.28%) All the vaginal hysterectomy was done for second- and third-degree utero-vaginal prolapse. Most prevalent endometrial histopathological finding in our study is non-secretive 15 (42.8%), secretive 7 (20%) followed by atrophic 6 (17.1%) as most of the patients in our study presents with abnormal uterine bleeding and menorrhagia 23 (65.7%).